The Effort of Caring: The Caregivers’ Perspective of Dual Sensory Impairment - Dunsmore, Moira E.; Schneider, Julie; McKenzie, Heather; Gillespie, James A. (Frontiers in Education, 2020)
Aim To explore the social experiences of Dual Sensory Impairment (DSI) for older Australian adults from the perspective of their family carers. Background DSI in older adults is a chronic progressive disability with varying combined degrees of vision and hearing loss. Prevalence increases with age and is particularly high in those > 85 years of age. Older persons with DSI experience a range of functional, social and emotional health issues and are considered a vulnerable group. Family carers fulfill complex multiple roles and provide the majority of care and support to this group. Caregiving and care-receiving are reported as demanding and stressful for both. Together, both spousal and mother-daughter dyads experience a range of social consequences as a result of DSI which are under-reported in the DSI literature. Design Qualitative study design using Grounded Theory Methodology (GTM). Methods This manuscript is part of a doctoral study. A total of 23 qualitative in-depth interviews with older Australians with DSI and their family carers were conducted over eighteen months. This manuscript reports on eight of those interviews (the caregivers) and explores the experiences of caregivers in the context of their relationship with their partner or parent with DSI. Data were analyzed using the inductive constant comparative method to systematically categorize emergent themes in order to develop a grounded theory. Findings This qualitative study reports on the social experiences of the family carer in the context of DSI, and identified social isolation, social effort and negotiating relationships as key themes. These common social effects interrupt personal and external social networks and have a pervasive, often negative impact on social relations and the care relationship itself. Conclusion The experience of living with DSI is underexplored from a caregiver’s perspective. Few studies explore the perspective of the family carer and the impact of their family member’s DSI on their immediate relationships and social experiences. This report draws on the experiences of eight family carers and identifies three main themes that impact the quality of their dyadic relationship. While caring in a DSI context has clear parallels to caring in other health domains, the social relational aspects of DSI appear unique justifying further qualitative exploration of the family carers’ perspective.